Conduct of clinical trials in the era of COVID-19 (2020)
The coronavirus disease-2019 (COVID-19) pandemic has profoundly changed clinical care and research, including the conduct of clinical trials, and the clinical research ecosystem will need to adapt to this transformed environment. The Heart Failure Academic Research Consortium is a partnership between the Heart Failure Collaboratory and the Academic Research Consortium, composed of academic investigators from the United States and Europe, patients, the U.S. Food and Drug Administration, the National Institutes of Health, and industry members. A series of meetings were convened to address the challenges caused by the COVID-19 pandemic, review options for maintaining or altering best practices, and establish key recommendations for the conduct and analysis of clinical trials for cardiovascular disease and heart failure. This paper summarizes the discussions and expert consensus recommendations. (J Am Coll Cardiol 2020;76:2368–78)